Ethnographing Historical Archives: Possible Ways to Research in Organization Studies - Lopes, Luma Louise Sousa; Ipiranga, Ana Silvia Rocha (Organizações & Sociedade, 2021)
Our objective in this article is to discuss the contributions of archival ethnography as a method of historical research in management. We indicate that, while historical research is already relevant in the management research area, there is still a dilemma regarding the possibility of how to access the past and conduct research of this nature. In this context, ethnography associated with historical archives emerges as a legitimate source, loaded with voices and silences to be unveiled in the processes of reflection on time in the context of organizations. Thus, we discuss the characteristics and possibilities of the method of an archival ethnography, considering its multi-situated character in the proposed research strategy. Thus, we hope to foster the discussion about ethnographic immersion in historical archives and how this method can contribute to the several research areas in management and more specifically in Organization Studies.